Makna Tradisi Sesajen dalam Pembangunan Rumah Masyarakat Jawa: (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2020)
The Meaning of the Tradition of Offerings in the Construction of Houses for the Javanese Community. A Case Study of Development in Srimulyo Village, Air Saleh District, Banyuasin Regency. This study aims to explain the process of implementing the offering tradition and reveal the meaning of offerings in the construction of Javanese community houses in Srimulyo village, Air Saleh sub-district, Banyuasin district. The method used is descriptive qualitative. Data collection techniques are observation, interviews, and documentation. The data analysis technique is to use structural analysis techniques. The results of the study showed that the types and forms of offerings used were fruits which meant that the results of human labor at work would be presented. And all these traditional offering activities are a manifestation of one's devotion and respect for God and every ritual has a meaning none other than asking for peace and serenity in life.